H HUBUNGAN PENGUASAAN MUFRADAT DAN QUWAID TERHADAP KEMAMPUAN MENULIS ARAB SISWA MAN 2 PALEMBANG - Abdul Aziz; Yuniar; Jamanudin (Irfani, 2025)
Arabic plays an important role in education, but many students have difficulty writing due to their weak mastery of basic grammar. This research aims to analyze the relationship between mastery of mufradat (vocabulary) and qawaid (grammar) on students' ability to write Arabic. This study was quantitative with a correlational design. The sample consisted of 31 students who answered a questionnaire containing 30 statements and a test to measure mastery of vocabulary, qawaid, and writing skills. Data analysis was conducted using validity, reliability (Cronbach's alpha), and Pearson correlation. All questionnaire items were declared valid. The results showed that 74.2% of students had good vocabulary mastery, 83.9% had a good understanding of qawaid, and 61.3% had good writing skills. The correlation test produced a correlation coefficient of 0.691, indicating a positive and significant relationship between vocabulary and qawaid mastery and writing ability. These findings emphasize the importance of mastering understanding and grammar as the basis for learning Arabic. This research is expected to contribute to teachers in developing effective learning strategies, as well as encouraging students to actively broaden their horizons and understand qawaid, in order to improve their Arabic writing skills accurately and communicatively.